Dynamics of Serum Pregenome RNA in Chronic Hepatitis B Patients Receiving 96-Month Nucleos(t)ide Analog Therapy - Tao, Yachao; Wang, Menglan; Liao, Juan; Cheng, Xing; He, Min; Zhang, Dongmei; Zhou, Taoyou; Chen, Jie; Chen, Enqiang; Tang, Hong (Frontiers in Medicine, 2022)
Background: Tissue covalently closed circular DNA (cccDNA) can reflect the activity of HBV replication. However, it is impractical to assess intrahepatic cccDNA in every outpatient. Serum pregenome RNA (pgRNA) is transcribed from intrahepatic cccDNA and may reflect the activity of intrahepatic cccDNA. We explored the dynamics and the potential role of serum pgRNA in patients receiving long-term NAs treatment. Methods: Serum pgRNA, HBV DNA, HBsAg, HBeAg and ALT levels were quantified, and the relationships between serum pgRNA and these common clinical indicators before and after the treatment were investigated. Results: Serum pgRNA showed dynamic change during the 96-month NAs therapy, and serum pgRNA levels were positive and detectable in 19 patients with undetectable serum HBV DNA. Serum pgRNA showed strong and positive correlation with serum HBV DNA (r= 0.693, p<0.001) and serum HBsAg levels (r= 0.621, p<0.001) at baseline. Patients with HBeAg seroconversion had lower baseline serum pgRNA levels (p=0.002). The area under the curve (AUC) of baseline serum pgRNA for predicting HBeAg seroconversion was 0.742 (95% CI: 0.606-0.850) with 63.16% sensitivity and 80.56% specificity. The cumulative HBeAg seroconversion rate was higher in patients with low serum pgRNA (p=0.001). Conclusions: Serum pgRNA of low level at baseline or great decline at month 6 may independently predict the high incidence of undetectable serum pgRNA at year 4 following NAs therapy, and the baseline serum pgRNA may serve as a novel predictor for HBeAg seroconversion during NAs therapy.